Analisis Penerapan Target Costing Sebagai Alat Pengendalian Biaya Produksi Dalam Upaya Meningkatkan Laba Pada CV Feljen Jaya Di Kota Manado - Rohani Kesya Lakaina; Harijanto Sabijono; Syermi S. E Mintalangi (GOING CONCERN : JURNAL RISET AKUNTANSI, 2023)
The general goal of a company is to be able to get maximum profit. Cost is one of the factors that affect profits so companies must understand exactly the financing process in order to increase production cost efficiency and maximize profits. Cost control can be done by the company by calculating or using the target costing method. This study aims to find out how the application of target costing as a means of controlling production costs and how the impact of the application of target costing on the company CV Feljen Jaya. The research method used in this study is qualitative method using descriptive analysis method. From the results of the study, it was found that by applying one of the target costing methods, namely value engineering on production costs, it can increase company profits. Profit in CV Feljen Jaya company after applying the target costing method can increase up to 5%, this is in accordance with what is expected by the company. Keywords : Target Costing, Production Cost, Profit